ANALISIS PERMINTAAN CABAI MERAH KERITING (Capsicum annum L) DI KOTA SEMARANG - SHOFIATUN SHOFIATUN; ROSSI PRABOWO; DEWI HASTUTI (MEDIAGRO, 2017)
ABSTRACT            Semarang city is the center of the entry of vegetables shipped from different cities in Central Java, one of which is a curly red  chili. This study aims to determine the demand curly red chili, factors affecting demand curly red chili, and the elasticity of demand curly red chili in the  Semarang City. The basic method uses the descriptive, analytical method. Decision purposive location in the Semarang City. The data are analyzed secondary data (time series) for 9 years (2006-2014). Data analysis using OLS (Ordinary Least Square) with multiple logarithmic function, to obtain the elasticity of demand. The results of data analysis using non-linear regression analysis model of static multiple. The results showed that the coefficient of determination (R2) of 97.9% means that the independent variable contribution is 97.9%, while the remaining 2.1% influenced by other variables not studied. F value of 28.452 with a significance value of 0.01 means real influence of independent variables on the dependent variable. The conclusion of this research that curly red chili requests each year has increased an average of 7.97% per year. Factors affecting included population of 0,011 significance level of 95%, the significance of revenues 0.028 with a confidence level 95%, the price of red chili significant is 0.075 with a confidence level of 90%. Elasticity of demand include the curly red chili the price elasticity coefficient -0.251inelastic means that changes in the asking price less than the price change, cross-price elasticity largered chili with a 0.481 coefficient is positive means the goods are substitutes and cross elasticity onion prices with negative sign coefficient -0.168means the goods are complementary the income elasticity coefficient 5.967 means marked positive meaning curly red chili are normal goods. Keywords: Curly Red Chili, Demand, Elasticity, Price, Semarang City.